Management Of Best Practices in Multinational Companies: Starbuck’s Best Practices in The Lebanese Market - Derghan, Mariam (Technium Business and Management, 2022)
This paper investigates how a Multinational Corporation (MNC), Starbucks in this case, adopts best practices to produce optimal results in the Lebanese market mentioning the difficulties and factors that influence the application of best practices. The ability of a MNC to effectively adapt a best practice to a host environment depends on the style of management of the company. After a face-to-face interview with the District Area Manager of the Starbucks Mena region and plenty of information gathered from the company's website and documents, Starbucks Lebanon adopts a combination of two different management styles introduced by Professor Howards: Polycentric and ethnocentric approaches.